2021
DOI: 10.3390/cancers13184584
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lenvatinib in Hepatocellular Carcinoma Patients with Liver Transplantation: A Case-Control Study

Abstract: Tumor recurrence is the most common cause of death in hepatocellular carcinoma (HCC) patients who received liver transplantation (LT). Recently, lenvatinib was approved for the systemic treatment of unresectable HCC patients; however, the role of lenvatinib in HCC patients after LT remains unclear. There were 56 patients with recurrent HCC after LT from 2008 to 2018 in our institute, and 10 patients who received lenvatinib were identified. Additionally, to understand the difference in the clinical impact of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The safety profiles of lenvatinib in patients with prior LT were consistent with the results of the REFLECT trial and other real‐world studies of lenvatinib in non‐LT HCC patients 8,13,15,31 . Although multiple immunosuppressants were used simultaneously with lenvatinib, no new safety signal was observed for lenvatinib in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The safety profiles of lenvatinib in patients with prior LT were consistent with the results of the REFLECT trial and other real‐world studies of lenvatinib in non‐LT HCC patients 8,13,15,31 . Although multiple immunosuppressants were used simultaneously with lenvatinib, no new safety signal was observed for lenvatinib in our study.…”
Section: Discussionsupporting
confidence: 88%
“…The safety profiles of lenvatinib in patients with prior LT were consistent with the results of the REFLECT trial and other real-world studies of lenvatinib in non-LT HCC patients. 8,13,15,31 T A B L E 3 Adverse events during lenvatinib treatment…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed the efficacy and safety of sorafenib and lenvatinib in patients with HCC [ 30 , 31 , 32 , 33 , 34 , 35 ]. Nevertheless, information on atezolizumab plus bevacizumab in real-world practice is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significant morbidity and mortality associated with HCC recurrence post-LT, it is important to have a better understanding of post-LT HCC recurrence across a wide range of patient cohorts [ 12 , 13 , 14 ]. Although there are observational studies that have evaluated HCC recurrence, survival, and mortality rate after a liver transplantation, they lacked proper secondary evidence.…”
Section: Introductionmentioning
confidence: 99%